2015
DOI: 10.1088/0953-8984/27/47/476002
|View full text |Cite
|
Sign up to set email alerts
|

From soft to hard magnetic Fe–Co–B by spontaneous strain: a combined first principles and thin film study

Abstract: In order to convert the well-known Fe-Co-B alloy from a soft to a hard magnet, we propose tetragonal strain by interstitial boron. Density functional theory reveals that when B atoms occupy octahedral interstitial sites, the bcc Fe-Co lattice is strained spontaneously. Such highly distorted Fe-Co is predicted to reach a strong magnetocrystalline anisotropy which may compete with shape anisotropy. To probe this theoretical suggestion experimentally, epitaxial films are examined. A spontaneous strain up to 5% la… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 74 publications
5
42
0
1
Order By: Relevance
“…Surface anisotropy contributions were finally evaluated by comparing anisotropy energies with a calculation for a bulk bct alloy with same lattice parameters and Brillouin zone integration on a grid of close to 100000 k-points (46x46x46). As shown in previous investigations 14,21 , epitaxially grown Fe-Co films with additions of 2 at% B or C exhibit spontaneous strain with c/a of approx. 1.03.…”
Section: Experimental and Theoretical Methodssupporting
confidence: 78%
See 1 more Smart Citation
“…Surface anisotropy contributions were finally evaluated by comparing anisotropy energies with a calculation for a bulk bct alloy with same lattice parameters and Brillouin zone integration on a grid of close to 100000 k-points (46x46x46). As shown in previous investigations 14,21 , epitaxially grown Fe-Co films with additions of 2 at% B or C exhibit spontaneous strain with c/a of approx. 1.03.…”
Section: Experimental and Theoretical Methodssupporting
confidence: 78%
“…Again, we argue, that the buffer induced strain relaxes during the film growth and only spontaneous strain remains. TEM observations confirm this statement 14,21 , since the c/a ratio measured close to the buffer interface does not vary significantly from the latter. It can be concluded that there is no influence of induced strain on the magnetic properties as no induced strain is left at the time of the magnetic ex situ measurements.…”
Section: Separating Volume and Faces Related Anisotropysupporting
confidence: 65%
“…For example, it was shown that a careful control of strain and alloy concentration allows for a large MAE in bct FeCo alloys [9][10][11][12] . The potential route to FeCo-based permanent magnets offered by that work inspired subsequent studies aiming to stabilize tetragonality in FeCo by B or C-impurities [13][14][15] . Also the tetragonal (Fe 1−x Co x ) 2 B compound has been carefully studied due to its tunable MAE as function of x [16][17][18][19][20] which, furthermore, has an intriguing temperature dependence 19,21,22 .…”
Section: Introductionmentioning
confidence: 99%
“…This is in accordance with the typical doping concentrations experimentally accomplishable, e.g., 12.5 at% content of N in Fe and 9.6 at% of B in Fe 0.38 Co 0.62 . [10,11] Like Fe-Co alloys, we find light interstitials can indeed cause stable tetragonal distortion to cubic full Heusler alloys, which is quantizated by the c/a ratio between the c-axis and in-plane lattice constants. As shown in Table 1, with N interstitials, Fe 2 NiAl has the a tetragonal distortion as large as c/a=1.57.…”
Section: Resultsmentioning
confidence: 87%
“…Nevertheless, due to the strong tendency for the FeCo alloys to relax, it is difficult to maintain the tetragonal distortion induced by the underlying substrates for thin films thicker than 2 nm [6,7,8]. Recently, following the prediction based on DFT calculations [9,10], systematic studies have been performed on FeCo+X (X= C and B), where spontaneous tetragonal distortions with c/a=1.04 can be induced by a few atomic percent interstitial doping of C or B atoms occupying the octahedral interstitial sites. The resulting MAE can be as large as 0.5 MJ/m 3 with B concentration up to 4 at%, where the tetragonal strain reaches 5%.…”
Section: Introductionmentioning
confidence: 99%